Polymer Design of Microwell Hydrogels Influences Epithelial–Mesenchymal Interactions During Human Bronchosphere Formation - Madeline K. Eiken; Justin E. Levine; Shinyeong Lee; Samantha Lukpat; Eleanor M. Plaster; Vikram Bala; Jason R. Spence; Claudia Loebel (Advanced NanoBiomed Research)
Bronchospheres have emerged as a promising in vitro model toward probing questions on organ development and disease. Several organoid models, including from airway (e.g., bronchial, tracheal) cells, require three‐dimensional (3D) Matrigel, a complex mouse tumor‐derived matrix that typically leads to heterogeneous size and structures. Synthetic and naturally derived polymeric hydrogels show increased opportunities as an alternative to Matrigel culture. In addition, recent advances in hydrogel‐based microcavities (i.e., microwells) have shown improved control over organoid size, structure, and composition. Here, we build upon this approach and describe the fabrication and characterization of microwell hydrogels based on other polymers, including diacrylated poly(ethylene glycol), agarose, methacrylated gelatin, and norbornene‐modified hyaluronic acid. Using these microwell hydrogels, human bronchial epithelial cells and lung fibroblasts readily assemble into viable cyst‐like bronchospheres. The study shows that the cellular composition regulates the formation and structure of the bronchosphere which also depends on the type and adhesiveness of the hydrogel. Furthermore, both hydrogel type and cellular composition influence the amount and composition of deposited extracellular matrix within the microwells. This hydrogel fabrication platform provides an accessible in vitro culture platform for the formation and growth of bronchospheres which can be extended to the culture of other organoid systems.